Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to compute $f'(x)$ where $f(x)=\log_{x}(x^2+3)$ ?

When we deal with $x^{x^x}$ we use $e^{x^x\ln x}$. What do we "do" with logarithms?

share|cite|improve this question
5  
Try using a change of base formula ($\log_b a={\ln a\over \ln b}$, e.g.). – David Mitra Jan 18 '13 at 16:39
1  
$f(x)=\log_u(u^2+3)$ has derivative $f'(x)=0$... :) – AndreasT Jan 18 '13 at 16:41
    
@AndreasT Why is that? From what David Mitra suggested I got $f'(x)= \frac{ \frac {2xlnx}{x^2+3} - \frac{ln(x^2+3)}{x}}{ln^2x}$ $= \frac{2u^2lnu-(u^2+3)ln(u^2+3)}{ln^2u}$ – Hagrid Jan 18 '13 at 17:01
    
@Hagrid I know, I was just joking about your mistyped variable $u$, for which $f$ would be constant. Your question has already been edited though... – AndreasT Jan 18 '13 at 17:04
    
Very nice :) Are my calculations in the comment above correct? – Hagrid Jan 18 '13 at 17:05
up vote 4 down vote accepted

Use the change-of-base formula: $$ \log_x (x^2+3) = \frac{\log_e (x^2+3)}{\log_e x}\quad\left(\text{or, if you like, }\frac{\ln(x^2+3)}{\ln x}\right). $$

share|cite|improve this answer

Let $y=f(x)=\log_{x}(x^2+3)\implies x^y=x^2+3$. Taking derivative on both sides gives, $$x^y(\frac{y}{x}+y'\log x)=2x\implies (x^2+3)(\frac{y}{x}+y'\log x)=2x$$ Now you can solve for $y'$ easily.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.